Lyapunov Inequalities for One-Dimensional p-Laplacian Problems with a Singular Weight Function. (2nd December 2009) - Sim, Inbo; Lee, Yong-Hoon
Abstract : We estimate Lyapunov inequalities for a single equation, a cycled system and a coupled system of one-dimensionalp -Laplacian problems with weight functions having stronger singularities thanL 1 .